The Validity of Guided Inqury-Based Teaching Materials on Management and Technique Laboratory - Yosi Laila Rahmi; Ardi Ardi; Ernie Novriyanti (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2017)
The study aimed to produce guided inquiry-based teaching materials for management and technique laboratory and to determine the validity of the teaching materials. The research was conducted using 3 (three) steps of a research and development (R&D) model. The instruments used in data collection in this research were questionnaire for student needed analysis and questionnaire to measure the teaching materials validity. The data obtained was quantitative from several validators. The validators consist of three lecturers. The percentage of a validity the teaching materials based on guided inquiry was 93.23 which can be categorized was very good.